Association of HLA-DRB1 and HLA-DQB1 with red-blood-cell alloimmunization in the Czech population - Maluskova, A; Mrazek, F; Pauliskova, M; Kovarova, P; Koristka, M; Jindra, P; Cermakova, Z (Vox sanguinis, 2017)
BACKGROUND AND OBJECTIVES: Alloimmune antibodies against red-blood-cell (RBC) antigens induced in susceptible individuals (responders) by transfusion, pregnancy or transplantation may have serious clinical consequences. The aim of this study was to investigate association of alloimmunization against selected RBC antigens with HLA-Class II. MATERIALS AND METHODS: A total of 230 responders (106 monoresponders and 124 multiresponders) were enrolled into the study. HLA-DRB1 and HLA-DQB1 variants were determined by PCR-SSO and their frequencies compared between the patients (patient subgroups) and 375 ethnically and regionally matched controls. RESULTS: Development of multiple RBC antibodies was associated with HLA-DRB1*15 and HLA-DQB1*06 allelic groups in the patients, with the relationship being particularly apparent in those with anti-C+D antibodies. Furthermore, DRB1*13 and DQB1*06 were more frequent in multiresponders with anti-E+c antibodies and DRB1*03 and DQB1*02 in those with anti-E+Cw. CONCLUSION: For the first time, we confirmed the association of HLA-DRB1*15 with RBC antibody multiresponder status and found HLA-Class II associations for three frequent RBC antibody combinations. Our data support the concept that HLA restriction plays an important role in the response to RBC alloantigens.
Keywords: alely; haplotypy; Humans; Pregnancy; HLA-DRB1 řetězec; Erythrocytes; HLA-DQ beta-Chains; transfusion medicine (in general); Female; dospělí; frekvence genu; Haplotypes; Alleles; Genotype; lidé; HLA-DRB1 Chains; HLA; Isoantibodies; Adult; HLA-DQ beta řetězec; ženské pohlaví; Male; těhotenství; Czech Republic; erytrocyty; Gene Frequency; red-blood-cell antigens and antibodies; genotyp; Česká republika; mužské pohlaví; isoprotilátky